The “I speaking/spoken”: Teachers who teach mathematics and the discourse on the intertwining between methodologies and technologies (Revista Contexto & Educação, 2026)
When we conduct research, we seek to understand and learn about the thinking of a collective, inserted in a culture. This type of investigation only occurs in one way, that is, through discursive testimony, through what the other can tell me. In this sense, the objective of this text is to present the Discourse of the Collective Subject as a methodological proposal that supports the analysis of a discourse by mathematics teachers about the intertwining of digital technologies and teaching methodologies. In addition, we present the proposal of the DSC in this search for understanding thinking, that is, from this instrument we can understand the thinking of a collective. In addition, we present the methodological steps and figures and also present some examples of these in and for the construction of a DSC in research. The study included 15 mathematics teachers who participated in an extension course offered to teachers in the region of the 18th Regional Education Coordination Office of the State of Rio Grande do Sul. Finally, the discussion leads us to reflect on the methodologies and instruments used in research on collective thinking, translating the social representations of several individuals who live in a culture.
Keywords: Discourse of the Collective Subjec; Research methodology; Digital Technologies; Discurso do Sujeito Coletivo